The effect of combined use of blood ultrafiltration and various priming solutions of cardipulmonary bypass on inflammatory markers in adult cardiac surgery - Клигуненко, Олена Миколаївна; Яровенко, Володимир Володимирович (ScienceRise: Medical Science, 2016)
Aim of the given research is to evaluate the influence of blood ultrafiltation during cardiopulmonary bypass (CPB) with primary circuit filling by various colloidal solutions on systemic inflammatory response markers in adult patients after heart valve replacement. Materials and methods. The study included 115 patients after heart valve replacement. They were randomly assigned into four groups depending on the type of fluid to fill the cardiopulmonary bypass (CPB) and blood ultrafiltration use. The first group (п=37) received modified gelatine 4 % solution for CPB filling. Hydroxyethylstarch 130/0,4 was administered in the original volume filling for the third group of patients (п=35). Blood ultrafiltration prior to CPB finishing was carried out in patients of second group (n=21) and fourth group (n=22). The inflammatory markers concentration (IL-1α, IL-6, TNF-a, IL-10) were studied in serum samples before intubation (1), after CPB finishing (2) and on the first day after surgery (3). The levels measurement (IL-1α, IL-6, TNF-a, IL-10) was carried out using commercially available enzyme-linked immunosorbent assay (Diaclone). Statistical data analysis was carried out using Statistica 6.0 with Schapiro, Wilkie, Wilcoxon, Kruskal-Wallis criteria (ANOVA by rank test). The value of p <0.05 was considered as reliable. Results. Any significant differences between groups in distribution according to age, male and female ratio, patients preoperative clinical status, CPB duration, and aortic clamp were not detected. Results have shown, that the TNF α and IL 6 levels in serum after CBP finishing and on the first day after surgery were considerably lower in the fourth group of patients. The IL-10 concentration in the fourth group was considerably higher after CBP and during the first day after surgery. The number of leukocytes increased in all groups, but it was considerably lower in the fourth group after CBP and during the first day after surgery. Besides, this group required shorter time of ventilation (р=0,0000), inotropic agents administration (р=0,02), intensive therapy unit (р=0,0018) and hospitalization (р=0,016,) comparing with the other groups. Conclusion. It has been fouond, that ultrafiltration removes from the circulating inflammatory cytokines and increases anti-inflammatory IL 10 level. It reduces the treatment duration and the number of complications